2014
DOI: 10.1161/hypertensionaha.113.02988
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Sympathoinhibitory Effects of Surgically Induced Weight Loss in Severe Obese Patients

Abstract: L ong-term prospective studies have recently shown that bariatric surgery significantly reduces the risk of death in severely obese patients.1 This has been confirmed by retrospective analyses of a large cohort of obese individuals in whom surgery-related reductions in body weight were associated with a significant reduction in death rate compared with obese individuals followed under dietary and medical treatment. [2][3][4] It is a widespread belief that the protective effect of bariatric surgery in obese pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 53 publications
6
64
0
2
Order By: Relevance
“…Similar results were noticed 6 mo and 1 yr after vertical sleeve gastrectomy where subjects showed in addition to metabolic and hemodynamic improvements, a substantial decrease in MSNA (142). The effects of sleeve gastrectomy on sympathetic tone may be mediated, at least in part, by the reduction in the elevated levels of plasma leptin but also by an improvement in baroreflex function (142). Surprisingly, it was recently documented that following gastric bypass surgery, despite the low-resting MSNA, there was an almost complete absence of sympathetic contribution to resting energy expenditure, suggesting that this may have important consequences for the maintenance of weight loss after gastric bypass (29) ( Table 1).…”
Section: Interventions To Treat Obesity and Their Role In Modulating supporting
confidence: 83%
See 1 more Smart Citation
“…Similar results were noticed 6 mo and 1 yr after vertical sleeve gastrectomy where subjects showed in addition to metabolic and hemodynamic improvements, a substantial decrease in MSNA (142). The effects of sleeve gastrectomy on sympathetic tone may be mediated, at least in part, by the reduction in the elevated levels of plasma leptin but also by an improvement in baroreflex function (142). Surprisingly, it was recently documented that following gastric bypass surgery, despite the low-resting MSNA, there was an almost complete absence of sympathetic contribution to resting energy expenditure, suggesting that this may have important consequences for the maintenance of weight loss after gastric bypass (29) ( Table 1).…”
Section: Interventions To Treat Obesity and Their Role In Modulating supporting
confidence: 83%
“…In addition, the weight loss was associated with a substantial reduction in MSNA and improvement in blood pressure and renal function (88). Similar results were noticed 6 mo and 1 yr after vertical sleeve gastrectomy where subjects showed in addition to metabolic and hemodynamic improvements, a substantial decrease in MSNA (142). The effects of sleeve gastrectomy on sympathetic tone may be mediated, at least in part, by the reduction in the elevated levels of plasma leptin but also by an improvement in baroreflex function (142).…”
Section: Interventions To Treat Obesity and Their Role In Modulating supporting
confidence: 59%
“…Seravalle et al [61] recently extended previous findings on the sympathetic nervous system in human hypertension and obesity with the demonstration of another beneficial effect of bariatric surgery, namely pronounced and sustained sympathoinhibition after gastric bypass in patients with severe obesity. Renal sympathetic denervation attenuates sodium and water retention and the rise in arterial pressure in a high-fat diet model of obesity in dogs.…”
Section: Sympathetic Nervous System Activity In Obesity-induced Hypermentioning
confidence: 77%
“…For instance, free fatty acids (FFAs) may represent a good candidate since one previous study [22] has found a correlation between the decline in circulating FFA levels and the QTc interval length reduction after diet-induced weight loss. Also, the adipose tissue hormone leptin may be a good candidate since it was shown to decline after bariatric surgery along with a marked reduction in SNS activity [43]. Beside these putative hormonal mediators, other mechanisms may also contribute to the weight loss associated reduction in QT interval length.…”
Section: Discussionmentioning
confidence: 99%